A method of summation of the Fourier-Jacobi series - Runovskii, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A summation method is constructed for the Fourier-Jacobi series, which has properties similar to the properties of the de la Vallée-Poussin methods of summation of the Fourier series by the trigonometric system.